Project SAYON (Student Aid Yielding Outstanding Numeracy): Enhancing Students’ Mathematical Proficiency - Anib, Jeoramy; Agno, Marvin; Milan , Kenneth Jhon; Mecarandayo, Angelica; Ganotise, Queenie Jane; Pahayahay, Aillen; Espinosa, Devyvon; Escandallo, Jonelson; Cerna, Conie; Muegna, Kristy Jane; Generalao, Regine (International Journal of Asian Education, 2026)
This study examined the effect of Project SAYON on the math proficiency of Grade 10 students at Luna National High School. Using a pre-experimental design, the study measured students' mathematical proficiency before and after the implementation of the project. The pre-test results showed a satisfactory level of proficiency, while the post-test results indicated a very satisfactory improvement. The findings revealed a significant difference between the pre-test and post-test scores, confirming the effectiveness of Project SAYON. The study concludes that Project SAYON is a valuable tool for enhancing math skills and recommends its adoption and expansion in the school curriculum. Additionally, it suggests regular teacher training, resource provision, and parental involvement to support the program's success. These findings highlight the potential of structured educational programs to significantly improve student performance in mathematics.